Training Needs for Mothers of children With Autism Spectrum Disorder and it’s Relation with Some Variables (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This study aims to investigate the needs of Mothers of Children with Autism Spectrum Disorder in Damascus, according to educational level of mothers, severity of autism and gender of child. The researcher adopted the descriptive approach to achieve the aim of the study. The sample consisted of (78) mothers selected randomly. The researcher developed a questionnaire to explore the needs of those mothers, the questionnaire was in two parts consisting of (46) items  the first part about theoretical knowledge it consisted of (20) items, the second  was about practical  skills it contained (26) items. The degree of validity and reliability of the questionnaire was good, so Cronbach's Alpha equation that which reach (0.97).. The findings of the study indicated, the degree of estimation of  mothers of children with autism disorder to their training needs is  high on theoretical knowledge domain and practical  skills domain and on the whole questionnaire.The results also showed there are statistically significant differences between degree of training needs of mothers attributed to  their educational level  and  to the  severity of the child's disorder , and there are no found   significant differences between degree of training needs of mothers attributable to gender of child.Based on the findings of the study the researcher pointed out the need of conducting more studies on new samples of mothers, with other variables, and on samples, including parents and brothers, and recommended increasing attention to training families of children with autism spectrum disorder, especially mothers, through the preparation of periodic training programs by centers that are concerned with these children.